Development of Ti-MCM-41 supported Bi-Metallic catalyst for hydrodeoxygenation of lignin derived bio oil model compounds / Murtala Maidamma Ambursa - Murtala Maidamma , Ambursa (2018)
The effective and efficient catalyst for hydrodeoxygenation of lignin derived bio oil has been the major challenge. To provide remedy to that, this research work aimed to developed effective modified supported Ni-Cu catalysts for hydrodeoxygenation of lignin derived bio oil via its model compounds (Guaiacol and Dibenzofuran). The catalysts development began with experimental studies begins with preliminary studies using metal oxides (CeO2, ZrO2 and TiO2) supported Cu-Ni catalysts at 250oC, 5MPa and 4 hours which screen out TiO2 species as a better support and hence provide basis for the synthesis of Ti-MCM-41 from MCM-41 by Ti incorporation through hydrothermal method followed by characterizations. The Cu-Ni/Ti-MCM-41 catalysts was also synthesized and optimized via Ni loading from 5 to 12.5%, characterized followed by hydrodeoxygenation of Guaiacol and dibenzofuran at 260oC, 10MPa and 6 hours after optimization of reaction parameters which revealed 7.5% Ni loading as the optimum catalysts. The influence of Ti loading on structure and activity was studies at which revealed 20wt.% Ti loading as the optimum. Then narrow optimization further revealed support Ti-MCM-41 with 18wt.% as the optimum Ti loading which was impregnated with Cu-Ni catalysts and compared with MCM-41 and TiO2 supported Cu-Ni catalysts for hydrodeoxygenation of guaiacol and dibenzofuran. The results showed that, Cu-Ni/Ti-MCM-41 catalysts, displayed higher activity than Cu-Ni/TiO2 and Cu-Ni/MCM-41 catalysts respectively. The reusability studies showed that, Cu-Ni/Ti-MCM-41 catalysts is stable for up to 4 cycles.